Turkey : Managing Labor Markets through the Economic Cycle - World Bank; Ministry of Development, Republic of Turkey (World Bank, Washington, DC, 2013)
The Turkish economy was hit hard by the global economic crisis, but recovered fast and strong. The economy had already started to slow down in 2007, but the global financial events of late 2008 led to a sharp contraction starting in the last quarter of 2008 until growth resumed in the last quarter of 2009. The recovery was rapid, with growth reaching 9 percent in 2010 and 8.5 percent in 2011. This study looks at how the labor market fared during the recent downturn and recovery and informs policies to manage labor markets through the economic cycle and address the jobs challenge in Turkey. The study investigates: 1) pre-crisis labor market trends and the structural jobs challenge in Turkey; 2) aggregate and distributional impacts of the recent crisis, and subsequent recovery, on the labor market; and 3) recent policy measures and existing labor market institutions in the context of observed labor market outcomes. Finally, the study links policies to manage labor markets through the cycle with measures to address the longer term, structural jobs challenge in Turkey. Ongoing structural transformations and the large 'stock' of low-skilled workers are behind the jobs challenge in Turkey. Continued urbanization and labor shedding in agriculture, along with the increase in the Working Age Population (WAP), will continue to increase the number of (mostly) young and low-skilled workers looking for non-agricultural jobs. The Turkish Employment Agency (ISKUR) plays a key role in activating low-skilled workers into productive employment. ISKUR has come a long way since 2008, increasing the coverage and quality of vocational training, introducing job and vocational counselors and linking social assistance receipts to registration in ISKUR.